Query Processing for Time Efficient Data Retrieval - Muhammad Qasim Memon; Jingsha He; Aasma Memon; Khurram Gulzar Rana; Muhammad Salman Pathan (Institute of Advanced Engineering and Science, 2018)
In database management system (DBMS) retrieving data through structure query language is an essential aspect to find better execution plan for performance. In this paper, we incorporated database objects to optimize query execution time and its cost by vanishing poorly SQL statements. We proposed a method of evolving and inserting database constraints as database objects embedded with queries either to add them for the sake of transactions required by user to detect those queries for the betterment of performance. We took analysis on several databases while processing queries itself and assimilate real time database workload with the bunch of transactions are invoked in comparison with tuning approaches. These database objects are coded in procedural language environment pertaining rules to make it worth and are merged into queries offering improved execution plan.